2021
DOI: 10.1039/d1em00032b
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and fate of per- and polyfluoroalkyl substances (PFAS) in wastewater treatment facilities

Abstract: Anthropogenic compounds known as per- and polyfluoroalkyl substances (PFAS) represent a major class of contaminants of emerging concern composed of nearly 5000 chemicals. Many PFAS are persistent, bioaccumulative and toxic,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 51 publications
7
31
0
Order By: Relevance
“…Higher summer temperatures have been shown to increase the removal of acesulfame and pharmaceuticals . Tavasoli et al found higher total measured PFAS concentrations in July than in March …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher summer temperatures have been shown to increase the removal of acesulfame and pharmaceuticals . Tavasoli et al found higher total measured PFAS concentrations in July than in March …”
Section: Methodsmentioning
confidence: 99%
“…On the basis of this scope, aqueous data were analyzed from 20 peer-reviewed articles, ,,,, , , one Water Research Foundation (WRF) technical report, one 3M report, and one state government report . Original data were also included for six WWTPs managed by a single utility in Virginia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different industrial wastewaters often have special emission inventories covering both legacy and alternative PFAS. PFAS concentrations from these different sources could vary temporally and spatially during individual wastewater treatment processes, depending on the physiochemical properties of the different PFAS present as well as their sensitivity to different treatment techniques. , Though industrial WWTPs directly receive PFAS containing wastewaters, water treatment facilities are rarely designed for PFAS removal . WWTP effluents and sludge are considered active sources for the environmental release of both legacy and alternative PFAS .…”
Section: Introductionmentioning
confidence: 99%
“…Beyond regulated wastewater contaminants, little data are publicly available assessing emerging contaminants derived from wastewaters discharging to the GBE and their downstream impacts. Perfluoroalkyl substance (PFAS) has been as stressor of interest in the region, with state data available and recent publications from our team assessing PFAS in wastewater, biosolids, and GBE surface waters (NHDES OneStop Database, n. d.; Adams et al, 2021;Tavasoli et al, 2021). Considering the potential individual and synergistic impacts of lowlevel PPCP concentrations on aquatic organisms (Di Poi et al, 2013;Meador et al, 2018), it is important to quantify PPCPs and other emerging contaminants in the estuary and their primary wastewater source.…”
Section: Introductionmentioning
confidence: 99%